Paul Gersmann. Alf Therkelsen. O. Tobiesen Meyer: Fra importregulering til moms. 1945-1986. Dansk Toldhistorie V. (Toldhistorisk Selskab, 1987). 506 s. - Meyer, Poul (Historie/Jyske Samlinger, 1989)
-